INFORMATION TECHNOLOGY IN PRIMARY EDUCATION AND ORGANIZING MULTIMEDIA LESSONS (British Journal of Global Ecology and Sustainable Development, 2023)
This article provides information on information and communication technologies, information on the organization of information technologies and multimedia lessons in primary education.